2022
DOI: 10.3390/ijms23158763
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and Film-Forming Properties of Chitosan Composites

Abstract: Chitosan (Chit) and its composite films are widely used in biomedical, cosmetic, and packaging applications. In addition, their properties can be improved and modified using various techniques. In this study, the effect of the type of clay in Chit composites on the structure, morphology, and physical properties of Chit solution and films was tested. The liquid flow properties of Chit solution with and without clay were carried out using the steady shear test. Chit films containing clay were obtained using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Polymer films, widely utilized in various applications, can improve their properties through a neutralization process [ 35 ]. This process is specifically designed to eliminate any residual solvents and unreacted cross-linking agents, resulting in overall enhancements in film performance.…”
Section: Discussionmentioning
confidence: 99%
“…Polymer films, widely utilized in various applications, can improve their properties through a neutralization process [ 35 ]. This process is specifically designed to eliminate any residual solvents and unreacted cross-linking agents, resulting in overall enhancements in film performance.…”
Section: Discussionmentioning
confidence: 99%
“…The result of SEM analysis for formic and acetic acid-based chitosan thin films in this study were comparable to the result obtained in the previous study conducted by [22], where the author concluded the result obtained show acid-based thin chitosan films exhibit a smooth and homogenous surface. Besides, the similar structure also can be found for other chitosan thin films dissolved in hydroxylated acid films such as lactic acid, citric acid and tartaric acid [23][24]. This occurrence can be explained by the strong intermolecular interaction between chitosan molecules and hydroxylated acid counter anions, which promoted the densification of the chitosan matrix and, as a result, could improve the homogeneity of the chitosan structure [25].…”
Section: Physical and Structural Properties Of Acetate And Formate Ch...mentioning
confidence: 58%
“…Interestingly, %DS enhanced in the cCSH film because of CNT addition, which might be attributed to ionic repulsion between protonated groups, the creation of hydrogen bonds between chitosan, and the intercalation of carbon nanotubes into the polymeric matrix and higher % DS may be because of the hydrophilic character of chitosan and the unbound polar groups in films interacting with water molecules [69]. Other authors reported that CNTs in the polymeric matrix reduce hydrophilicity [70].…”
Section: Swelling Degreementioning
confidence: 95%
“…Our results agree with typical values for three-dimensional polymeric networks capable of swelling without the rupture of their structure. The measurement was carried out after 48 h, during which the absorption equilibrium was achieved [69]. We noticed a maximum swelling percentage of 798% for CSM and 747% for CSH (Fig.…”
Section: Swelling Degreementioning
confidence: 95%